2012
DOI: 10.1111/j.1745-4549.2012.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL CHANGES IN WASHED MINCE OF SILVER CARP (HYPOPHTHALMICHTHYS MOLITRIX ) DURING FROZEN STORAGE AT −20C WITH OR WITHOUT CRYOPROTECTANTS

Abstract: Studies were conducted to assess the chemical and quality changes in washed silver carp mince when frozen and stored at −20C with or without cryoprotectants. A previous washing step has led to a positive effect on fish quality according to marked content decreases in expressible moisture, volatile basic amines, free fatty acids and thiobarbituric acid reactive substances; such quality performances were maintained throughout the frozen storage. On the other hand, addition of cryoprotectants enhanced the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…This change could promote the increment of myofibrillar proteins and finally as a result of these changes, the water retention capacity was increased (Biscalchin-Grÿ schek et al , 2003). However, the moisture content M (71.3%) was lower than that reported in other mince species; for instance, 77.1% was documented in mackerel muscle mince (Eymard et al, 2009), 78.7% in muscle mince carp (Majumdar et al, 2012), and 81.3 and 78.3% in tilapia mince backbones (Oliveira et al, 2012;Kirschnik et al, 2013).…”
Section: Physicochemicalmentioning
confidence: 62%
See 2 more Smart Citations
“…This change could promote the increment of myofibrillar proteins and finally as a result of these changes, the water retention capacity was increased (Biscalchin-Grÿ schek et al , 2003). However, the moisture content M (71.3%) was lower than that reported in other mince species; for instance, 77.1% was documented in mackerel muscle mince (Eymard et al, 2009), 78.7% in muscle mince carp (Majumdar et al, 2012), and 81.3 and 78.3% in tilapia mince backbones (Oliveira et al, 2012;Kirschnik et al, 2013).…”
Section: Physicochemicalmentioning
confidence: 62%
“…Biscalchin-Grÿ schek et al (2003) observed a gradual increase in pH on washed tilapia-muscle mince, and argued that this pattern can continue if additional wash cycles are performed. Higher pH values in washed mince may occur due to the removal of free fatty acids, free amino acids, lactic acid and other water-soluble acidic substances (Majumdar et al, 2012). The initial values of pH were 7.2, 7.2, 7.4 and 7.7 for M, MW, MC and MWC, respectively.…”
Section: Physicochemicalmentioning
confidence: 94%
See 1 more Smart Citation
“…A three-dimensional gel network is subsequently developed when unfolded proteins undergo aggregation as induced by heat (Petcharat & Benjakul, 2017). Both dark-and whitefleshed fishes, including fresh water and marine fishes, have commonly been used in surimi production, such as lizardfish (Benjakul, Visessanguan, Tueksuban, & Tanaka, 2004), bigeye snapper (Julavittayanukul, Benjakul, & Visessanguan, 2006), tilapia (Rawdkuen, Sai-Ut, Khamsorn, Chaijan, & Benjakul, 2009), mackerel (Balange & Benjakul, 2009), croaker (Panpipat, Chaijan, & Benjakul, 2010), Alaska pollock (Yin & Park, 2014), silver carp (Majumdar, Deb, Dhar, & Priyadarshini, 2013), and common carp (Ganesh, Dileep, Shamasundar, & Singh, 2006). Sardine (Sardinella albella) is one of This article was published on AA publication on: 20 May 2019 the pelagic dark-muscled fishes, which has been used as an alternative raw material for surimi production.…”
Section: Introductionmentioning
confidence: 99%
“…Washing reduced total protein content which may be explained as the removal of sarcoplasmic protein during washing which makes up to 20 % to 25 % of total protein of fish muscles (Negbenebor et al 1999;Taskaya et al 2003). Majumdar et al (2012) also reported a significant decrease of protein content after washing of silver carp mince. Removal of sarcoplasmic proteins may result increased concentration of myofibrillar proteins followed by improved water holding capacity of meat, because of increased hydration of protein due to removal of blood, pigments, proteins etc.…”
Section: −1mentioning
confidence: 96%